Jewish converts, their communities and experiences of social inclusion and exclusion in post-apartheid South Africa - Kriel, Elli (Department of Sociology, 2017)
Set in a small minority community in South Africa, the Orthodox Jewish com-munity in Johannesburg, this study explores why a person would actively and volun-tarily seek minority status by converting into an ethnic-religious minority group. Taking a social constructionist approach to understanding religious conversion, it is argued that religious conversion to Orthodox Judaism is also a social process of becoming ethnically "Jewish". In this study, two types of converts are considered, namely con-verts who come to Judaism through marriage and converts for religious purposes. Through in-depth-interviews with rabbis and converts, experiences of social inclusion and exclusion, and the meaning of conversions is understood. This study finds that regardless of the path to conversion, belonging and identity are key reasons for con-version, and that it is an ethnic process that serves group and individual needs recip-rocally. At an individual level, becoming Jewish through conversion helps avoid social exclusion and achieves other social inclusions by acquiring membership in new com-munities and by forming new social identities. At a group level, the research shows that religious conversion is part of the group's broader concern for maintaining ethnic boundaries and is therefore an element of the politics of belonging. The research shows how conversion to a minority ethnic group in a plural environment becomes a social means to protect ethnic identity and avoid assimilation. By understanding con-version as the politics of belonging, the research explores the subjective experiences of citizenship at a group and individual level.